Escherichia coli response to subinhibitory concentrations of colistin: insights from a study of membrane dynamics and morphology. (12th April 2022) - Ilangumaran Ponmalar, Ilanila; Swain, Jitendriya; Basu, Jaydeep K.
Abstract : Sublethal doses of colistin alters the membrane dynamics through surface interactions. Abstract : Prevalence of widespread bacterial infections brings forth a critical need to understand the molecular mechanisms of the antibiotics as well as the bacterial response to those antibiotics. Improper use of antibiotics, which can be in sub-lethal concentrations is one among the multiple reasons for acquiring antibiotic resistance which makes it vital to understand the bacterial response towards sub-lethal concentrations of antibiotics. In this work, we have used colistin, a well-known membrane active antibiotic used to treat severe bacterial infections and explored the impact of its sub-minimum inhibitory concentration (MIC) on the lipid membrane dynamics and morphological changes of E. coli . Upon investigation of live cell membrane properties such as lipid dynamics using fluorescence correlation spectroscopy, we observed that colistin disrupts the lipid membrane at sub-MIC by altering the lipid diffusivity. Interestingly, filamentation-like cell elongation was observed upon colistin treatment which led to further exploration of surface morphology with the help of atomic force spectroscopy. The changes in the surface roughness upon colistin treatment provides additional insight on the colistin–membrane interaction corroborating with the altered lipid diffusion. Although altered lipid dynamics could be attributed to an outcome of lipid rearrangement due to direct disruption by antibiotic molecules on the membrane or an indirect consequence of disruptions in lipid biosynthetic pathways, we were able to ascertain that altered bacterial membrane dynamics is due to direct disruptions. Our results provide a broad overview on the consequence of the cyclic polypeptide colistin on membrane-specific lipid dynamics and morphology of a live Gram-negative bacterial cell.